Supraphysiological Role of Melatonin Over Vascular Dysfunction of Pregnancy, a New Therapeutic Agent? - Valenzuela-Melgarejo, Francisco J.; Lagunas, Constanza; Carmona-Pastén, Fabiola; Jara-Medina, Kevins; Delgado, Gustavo (Frontiers in Physiology, 2021)
The temporal desynchronization of cell proliferation, differentiation, invasion from trophoblast cells results in vascular insufficiencies. This impairment can elevate the risk of poor fetal/placental development by Preeclampsia, intrauterine growth restriction, and preterm birth. Melatonin has antioxidant, homeostatic, and time-giving roles in the circadian system and physiology. Synthesized by the maternal pineal gland during night hours can cross the placental barrier, synchronizing the placenta and fetus's physiological functions. During the early placental development, a critical event is pro-angiogenic factors and the antioxidant system's activation. Mothers with a low level of Melatonin showed low levels of pro-angiogenic factor VEGF, such as shift works or light exposition during dark hours and finally increasing the risk of Preeclampsia, premature birth, and abortion. Melatonin supplementation can reduce the systolic pressure, prevents the oxidative-stress inducing the activation of antioxidant via, and lessen the proteinuria and serum level of sFlt-1. Besides elevates the serum levels of PIGF and inhibit the adverse outcomes over placental weight induced by the oxidative stress. At the placenta level, Melatonin can repair the endothelial damage from Preeclampsia, increasing the level of PIGF, Nrf-2, HO-1, and reducing sFLT-1, all that are critical markers of vascular injury during the pregnancy. At the placental blood flow level, Melatonin supplementation restores the umbilical and uterine artery's pulsatility index and blood-flow after oxidative stress induced. Curiously, these beneficial effects over pathological pregnancies can partially observe in normal pregnancies. The dual role of Melatonin over placental physiology could be the future for the protection and therapeutic application in vascular pathologies of pregnancies.